ANALYSIS OF OHMIC HEATER EFFICIENCY IN THE PRODUCTION OF LIQUID PALM SUGAR BASED ON FREQUENCY AND POWER - Rucitra Widyasari; Bambang Dwi Argo; Anang Lastriyanto; Susinggih Wijana (Jurnal Teknologi Pertanian, 2025)
Arenga sap is traditionally evaporated to produce liquid palm sugar. This process takes a time-consuming, energy-intensive, and results in varying quality. As an alternative technology, ohmic heating is expected to improve product quality by analyzing frequency and power variations to control temperature, current strength, and the quality of liquid sugar from arenga sap, compared to conventional methods. The study shows that increasing the frequency and power speeds up the evaporation process, which improves efficiency during ohmic heating. Efficiency is measured in three phases: the temperature increase phase, the temperature stability phase, and the temperature decrease phase. At a frequency of 250 Hz and 120 W, the highest efficiency recorded is 68.06%, with an average of 24.33%. This high efficiency also indicates that the quality of the liquid sugar produced from the arenga palm sap is improved, due to less damage to its functional properties.